Strategies Applied in Resolving Organizational Conflict in the Academe: An Experienced-based Approach - Cajayon, Menrado V.; Gutierrez, Ernell Bautista; Masanga, Luisito P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
There is no organization with no conflict situations (Kharadze & Gulua (2023), thus, this research identified and analysed organizational conflict in the subject institution. It further investigated the effectiveness of conflict resolution as practiced by the select organization. The study is qualitative in nature and utilized twelve (12) key informants selected by way of purposive sampling. Results revealed common organizational conflicts, strategies and suggestions based on the experience of the select key informants. The following organizational conflicts were culled out: Misinterpretation/Misunderstanding, Failure to Comply, Leadership Conflict, Professional Rivalry, Work Load Distribution and Undesirable Decision-making. On the other hand, the following are the common strategies applied to solve organizational conflict: Teambuilding, One-on-One Interaction, Portraying Positive Disposition, Identifying and Eradicating Root Causes and Policy Re-orientation. Lastly, the following are suggested by the key informants to lessen if not to solve organizational conflict: Socialization Activities, Collaborative Activities, Expert Advice, Helpful Attitude and Openness and Honesty.